2021
DOI: 10.3390/nu13103307
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Branched-Chain Amino Acids (BCAAs) and Cardiometabolic Risk Factors in Middle-Aged Caucasian Women Stratified According to Glycemic Status

Abstract: We examined the glycemic status-stratified relationships between total serum branched-chain amino acid (BCAA) concentrations and cardiometabolic risk factors in middle-aged Caucasian women. The study included 349 women divided into 2 subgroups: a normoglycemic group (NG, n = 184) and a dysglycemic group (DG, n = 165). Blood samples, anthropometric parameters, and blood pressure were measured. HOMA-IR, albumin-corrected calcium (CCa), and fatty liver index (FLI) were calculated. BCAA concentrations were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 93 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…According to a recent study conducted in Poland to evaluate the prevalence of dyslipidemia in the adult population, elevated triglyceride levels (>150 mg/dL) were observed in 31% of men and 20% of women [17], while in our study, this proportion was almost the same, with hypertriglyceridemia present in 29.4% of men and 19.7% of women. We did not assess either thyroid function or insulin resistance in our study; however, referring to recent data from our group, we may assume that most of the subjects were euthyroid [19]. Moreover, in our study, both females and males had similar glycemic status according to HbA1c values.…”
Section: Discussionmentioning
confidence: 74%
“…According to a recent study conducted in Poland to evaluate the prevalence of dyslipidemia in the adult population, elevated triglyceride levels (>150 mg/dL) were observed in 31% of men and 20% of women [17], while in our study, this proportion was almost the same, with hypertriglyceridemia present in 29.4% of men and 19.7% of women. We did not assess either thyroid function or insulin resistance in our study; however, referring to recent data from our group, we may assume that most of the subjects were euthyroid [19]. Moreover, in our study, both females and males had similar glycemic status according to HbA1c values.…”
Section: Discussionmentioning
confidence: 74%
“…We believe this does not affect our results at first, as in our study the borderline correlation of ANGPTL3 with TG/HDL-C ratio was observed only in POST women (p = 0.055), secondly as the cut-off point for this ratio which may vary depending on the glycemic status [27] was similar in PRE and POST cases. We did not assess insulin resistance but, referring to our previous study in which both, TG/HDL-C index and HOMA-IR (the homeostasis model assessment-estimated insulin resistance) were calculated, it is safe to assume that in most women HOMA-IR was within the reference range [28]. Moreover, recent review articles reported that insulin does not alter ANGPTL8 levels in the circulation [9] and that the association of ANGPTL8 with insulin resistance and HbA1c in non-diabetic subjects seems contentious [29].…”
Section: Discussionmentioning
confidence: 99%
“…Fasting venous blood samples were collected in the early morning for all parameters. The parameters of triglycerides (TG), HDL-cholesterol (HDL-C), creatinine, CRP, alanine aminotransferase (ALT), gamma glutamyltransferase (GGT), insulin, and TSH were measured in the serum, while the plasma was used for glucose measurement, and EDTA whole blood was used to determine glycated hemoglobin (HbA1c) as previously described [50]. The HOMA-IR value was calculated [51].…”
Section: Blood Sampling and Laboratory Analysesmentioning
confidence: 99%